DIVERSITY OF JUGLANDACEAE IN CUC PHUONG NATIONAL PARK - Van Sam, Hoang; Thi Duong, Dao; Truong Son, Nguyen (Journal of Forestry Science and Technology, 2021)
This paper provides information regarding diversity and conservation of Juglandaceae in Cuc Phuong National Park. Based on inventory and measurement of general characters, results indicated that there were four walnut species distributed in Cuc Phuong National Park, belonging to four genera. Alfaroa roxburghiana (Lindl. ex Wall.) Iljinsk, Carya sinensis Dode & Zucc, Platycarya strobilacea Siebold and Pteracarya tonkinensis Dode. The number of Walnut species in Cuc Phuong national park account for 36% of the total Walnut species and 57% of general species in Vietnam. Most species are distributed between 100 m – 600 m above sea level in the study site. Juglandaceae species in Cuc Phuong are of high conservation value with three species on the IUCN Red List (2020) and one species in Viet Nam Red Data Book (2007). The Platycarya strobilacea Siebold is not listed on the IUCN Red List and Viet Nam Red Data Book, but it is known to be very rare in the park. This research also provides information on the morphological and ecological characteristics of four walnut species in the study site.